Digital Empowerment through Community Orientation: Evaluating Consumer Adoption of a Municipal Waterworks Service Application - Cruz, Michael Marvin; Dandan, Dexter; Agraviador, Dino; Clarido, Clint; Balogo, Ken (International Journal of Interdisciplinary Viewpoints, 2026)
This study examines the impact of a community-based digital orientation program implemented by the College of Computer Studies of Central Philippine State University (CPSU) San Carlos Campus in partnership with the local government unit of the Municipality of Calatrava, Negros Occidental, Philippines. The initiative involved the development and deployment of a municipal waterworks service application designed to improve service delivery and address inefficiencies associated with manual processes. The program aimed to equip consumers with the knowledge and skills necessary to effectively utilize the application. A descriptive research design was employed, with data collected from 55 waterworks consumers in Barangay San Isidro who participated in the orientation. A structured questionnaire was used to assess awareness, digital confidence, ease of use, application’s usefulness, and consumers’ intention to use. Descriptive statistical tools, including weighted mean and ranking, were applied in the analysis. Findings revealed very high levels across all variables, indicating strong positive perceptions of the application. The usefulness of the developed application emerged as the most influential factor, underscoring the importance of practical benefits in driving adoption. The results further highlight the role of structured orientation in enhancing user readiness and engagement. Overall, the study demonstrates that extension programs can effectively bridge the gap between technological innovation and community utilization, promoting digital inclusion and improved public service delivery.